2020
DOI: 10.1108/jhass-06-2020-0088
|View full text |Cite
|
Sign up to set email alerts
|

Population growth and human resource utilization nexus in Nigeria

Abstract: Purpose Population growth has remained a key issue facing developing economies in the world. While developed countries are experiencing diminished or negative population growth, many countries in sub-Saharan Africa including Nigeria are having population growth above the economic growth rate. With the deadline for the sustainable development goals approaching, attention is increasingly being focused on population growth and human capital development. Extant literature focused on population growth, human resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
(55 reference statements)
2
6
0
Order By: Relevance
“…This adversely affects investment; consequently, employment is adversely effected. This finding corroborates evidence from Maijama'a et al (2019), Afolabi and Awopetu (2020), Adeosun and Popogbe (2020) which found that increase in population worsens the unemployment problem in the country.…”
Section: Model Estimation Resultssupporting
confidence: 92%
“…This adversely affects investment; consequently, employment is adversely effected. This finding corroborates evidence from Maijama'a et al (2019), Afolabi and Awopetu (2020), Adeosun and Popogbe (2020) which found that increase in population worsens the unemployment problem in the country.…”
Section: Model Estimation Resultssupporting
confidence: 92%
“…Thus, an increase in population does not necessarily translate to better economic growth. This corroborates the findings by Adeosun and Popogbe (2020). The error correction term is À1.7, which is statistically significant at 1%, suggests a 172% annual adjustment toward long-run equilibrium.…”
Section: Autoregressive Distributed Lag Estimationsupporting
confidence: 90%
“…On the other hand, Vecchione (2018) focused on the Italian economy and found that high skilled migration drastically reduced human capital accumulation in Italy The findings showed that migration negatively impacted human capital development. These findings imply that the problem of human development may be a cause and effect of human capital flight as revealed by Tabassum et al (2017), Adeosun and Popogbe (2020); and Popogbe and Adeosun (2020). The study by Docquier and Rapoport (2012) further revealed that uncontrolled high-skilled migration led to a shortage of health workers in Sub-Saharan Africa in 2010, which, in turn, led to worsened health status.…”
Section: Human Capital Flight and Output Growthmentioning
confidence: 81%
See 1 more Smart Citation
“…There are many papers dealing with economic growth in time series (Narayan et al, 2007;Payne, 2010;Wong, 2013;Sa Cardoso and Ravishankar, 2015), while others focus on population (Azam et al, 2020;Adeosun and Popogbe, 2020), and others on the relationship between them (Yezdani, 2013;Rehman, 2019). In general, there is agreement on the existence of a relationship between population and GDP per capita and its importance to understand income per capita distributions.…”
Section: Literature Reviewmentioning
confidence: 99%